ANTIBODY RESPONSE OF BROILERS TO CELL CULTURE ADAPTED THERMOSTABLE NEWCASTLE DISEASE I-2 STRAIN VACCINE - F. Siddique; M. S. Mahmood; I. Hussain; F. Deeba (Journal of Animal and Plant Sciences, 2015)
The efficacy of cell culture adapted thermostable Newcastle disease virus vaccinal strain I-2 was evaluated at various commercial poultry (broiler) farms. Day-old chicks (n=360/6 farms) were vaccinated (oral route) and blood sample from each bird was collected for serum separation. Antibody response was monitored through haemagglutination inhibition test (HI) and enzyme linked immunosorbant assay (ELISA) on 0, 7, 14, 21, 28 and 35 days post-vaccination (DPV). Maximum geometric mean anti-NDV-HI (Log27.83) and anti-NDV-ELISA (6017) antibodies titers were observed, respectively on 14th DPV. It was observed that administration of NDV I-2 strain vaccine in broilers birds is feasible and was found to induce more protective antibody response. Thermostable NDV I-2 strain can be a preferred choice against NDV in developing countries.
Keywords: Thermostable; Antibody; ELISA; Titer; Serum